Typology of native species as the shade tree for merbau (Intsia bijuga) plantations in Papua, Indonesia based on ecological species group - ELIESER VIKTOR SIRAMI; DJOKO MARSONO; RONGGO SADONO; MUHAMMAD ALI IMRON (Biodiversitas Journal of Biological Diversity, 2019)
Sirami EV, Marsono Dj, Sadono R, Imron MA. 2019. Typology of native species as the shade tree for merbau (Intsia bijuga) plantations in Papua, Indonesia based on ecological species group. Biodiversitas 20: 43-53. Ecological species group is an ecological principle that can be used as a reference in determining the potential native tree species of Papua as the shade trees for merbau in the mixed forest plantations. This research was conducted to identify the potential native trees as the shade for merbau plantation in Papua. The data collection used systematic line technique with hypothetical plot and sampling tree as the plot center. The Dice Index was used to analyze the level of association between merbau and the neighboring trees as well as to serve as a basis for determining ESG and Important Value Index was used to analyze the level of tree dominance. The main potential shade trees consisting of Pometia coriacea Radlk., Lepiniopsis ternatensi Valeton, Spathiostemon javensis Blume, Palaquium amboinense Burck., and Pimelodendron amboinicum Hassk. Whereas complementary and alternative potential shade consisting of Haplolobus lanceolatus H.J.Lam ex Leenh, Haplolobus celebicus H.J.Lam, Horsfieldia laevigata Warb., Horsfieldia irya (Gaertn.)Warb. Prunus costata Kalkman, Sterculia macrophylla Vent., Dysoxylum mollissimum Blume, Pertusadina multifolia (Havil.) Ridsdale, Streblus elongatus (Miq.) Corner and Geijera salicifolia Schott. The main shade trees possessed a main function for rendering shade toward younger merbau in the plantation area. Meanwhile, complementary and alternative shade trees were intended for increasing soil nutrient availability and optimizing microclimate surround merbau seedlings.